PENERAPAN PENCATATAN KEUANGAN PADA INDUSTRI KECIL RUMAHAN : Studi Kasus pengusaha laundry kiloan “Laundry Pelangi” Surabaya - Permatasari, Indah Agustin (Yayasan Education and Social Center, 2024)
The 2020 economy is heavily influenced by economic and political conditions. Indonesia is a developing country that does not rule out the possibility of technology that provides convenience, such as completing daily tasks which used to be the responsibility of each individual in completing daily routines. Because of the various activities that cause time to be limited, washing clothes becomes a problem for everyone, so they decide to do laundry in the laundry. However, there are currently many laundry businesses that have gone bankrupt. This is because there is a lot of competition that occurs in these businesses, such as poor service and financial management systems. So it is proven based on phenomena in the field showing that the perpetrators of clothing laundry entrepreneurs do not understand good and correct accounting records, they consider the recording to be too complicated to carry out and only do very simple records and perform rough calculations with the system. clothes laundry business finances with other businesses. Small and medium-sized enterprises (SMEs) are identical with the lack of awareness to carry out bookkeeping properly in the business world. With a lack of knowledge in bookkeeping, it automatically prevents them from carrying out financial bookkeeping activities. This study aims to determine the application of financial records in small home-based industries and to find out the extent to which laundry entrepreneurs understand accounting. The method used is a qualitative method to explore and explain the application of financial records in small cottage industries. Based on the observation that it was found that entrepreneurs were able to make financial records according to their own knowledge and understanding and had not applied the Statement of Financial Accounting Standards (PSAK) entrepreneurs made notes on their business financial statements according to their needs and abilities, this was done because they thought how their business would survive. and to grow and increase their income